Structured light enhanced entoptic stimuli for vision science applications - Pushin, Dmitry A.; Cory, David G.; Kapahi, Connor; Kulmaganbetov, Mukhit; Mungalsingh, Melanie; Silva, Andrew E.; Singh, Taranjit; Thompson, Benjamin; Sarenac, Dusan (Frontiers in Neuroscience, 2023)
The dichroic macular pigment in the Henle fiber layer in the fovea enables humans to perceive entoptic phenomena when viewing polarized blue light. In the standard case of linearly polarized stimuli, a faint bowtie-like pattern known as the Haidinger's brush appears in the central point of fixation. As the shape and clarity of the perceived signal is directly related to the health of the macula, Haidinger's brush has been used as a diagnostic marker in studies of early stage macular degeneration and central field visual dysfunction. However, due to the weak nature of the perceived signal the perception of the Haidinger's brush has not been integrated with modern clinical methods. Recent attempts have been made to increase the strength of the perceived signal by employing structured light with spatially varying polarization profiles. Here we review the advancements with the structured light stimuli and describe the current challenges and future prospects.